O uso do computador, a alfabetização e a pós-alfabetização: o que dizem educando/as do MOVA - Gonçalves, Becky Henriette (2006)
The present study aims, as it main goal, to anlyze the contribuitions of the utilization of computer to the literacy and postliteracy of teens and adults and for the superation of self-protection. Yet abording the new tendencies imposed by the Information Society or Informacional Capitalist Society. From documents, theoretical references, observations and discussions with the students in alphabetical and post alphabetical situation and using the computer as one more tool in this process of teaching-learning, it was found that such tool has many benefits for lecture and writen acquisition for the process of escolarization of teens and adults, as well as it makes possible an insertion, yet as initial in the Information Society, and qualification for jobs, that in the actual context demands to deel with much more with those new information and comunication tecnologies. Thus, as they notice historical subjects and capable of transformation, alphabetized, social and economical inserted, the students surpass the social speech built by them, of self-protection. Looking foward to contribute with the teaching of teens and adults in the acquisition of lecture and writing for a critical concept and world transform, this study alerts for the using of the computer in the process of alfabetization and post-alfabetization of teens and adults is an instrument with big contributions, wich points the necessity of elaboration and implementation of public politics in this way of inclusion and superation of social inaquilities and educatives.